Unemployment scarring in the early career : do skills and labour demand matter? - Hänni, Miriam [Verfasser]; Kriesi, Irene [Verfasser] (My University, 2025)
„Rocky school‐to‐work transition processes, characterized by spells of unemployment and education–job mismatch, can have long‐lasting scarring effects on young people and often lead to a loss of income and occupational status. However, the mechanisms that either foster or prevent unemployment scarring are underinvestigated. Our article thus asks whether vocational education and training (VET) diploma holders’ unemployment duration and the probability of status loss at labour market re‐entry are affected by the interplay between occupation‐specific labour demand and young workers’ skill sets acquired in VET. Our theoretical approach combines job search, human capital, and signalling theory with arguments from structural segmentation approaches. Our analyses use complete national register data on VET diploma holders who became unemployed during their early careers. We combine national register data on unemployment spells with register data on education trajectories in Switzerland and occupation‐specific labour demand data. Results from event‐history analyses indicate that unemployment episodes are associated with lower employment chances and higher risk of status loss of VET diploma holders. These general patterns are attenuated by occupation‐specific labour demand and the skills taught in vocational training programmes. Re‐employment chances are higher and the risk of status loss lower when occupation‐specific labour demand is high and few of the accessible job opportunities offer lower status than the job before unemployment. Additionally, we find that workers who trained in occupations imparting large proportions of occupation‐specific skills have a higher re‐employment probability but also face a higher risk of status loss than those who trained in occupations imparting larger proportions of general skills. Our findings indicate a trade‐off between occupation‐specific skills and general skills.” (authors’ abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 1.3.2.2 Übergänge; G 1.2.2.4 Arbeitslosigkeit; G 1.2.3 Qualifikationsentwicklungen; G 1.3.3 Bildungs- & Erwerbsbiografien; 370; Jugendlicher; Berufseinmündung; Arbeitslosigkeit; Dauer; Einflussfaktor; Beruflicher Status; Berufliche Qualifikation; Ausbildungsplatznachfrage; Berufsverlauf; Schweiz